Genetic study of resistance to charcoal rot and Fusarium stalk rot diseases of sorghum - Adeyanju, Adedayo (Kansas State University, 2014)
Fusarium stalk rot and charcoal rot caused by Fusarium thapsinum and Macrophomina phaseolina respectively are devastating global diseases in sorghum that lead to severe quality and yield loss each year. In this study, three sets of interrelated experiments were conducted that will potentially lead to the development of resistance based control option to these diseases. The first experiment was aimed at identifying sources of resistance to infection by M. phaseolina and F. thapsinum in a diverse panel of 300 sorghum genotypes. The genotypes were evaluated in three environments following artificial inoculation. Out of a total of 300 genotypes evaluated, 95 genotypes were found to have resistance to M. phaseolina and 77 to F. thapsinum of which 53 genotypes were resistant to both pathogens. In the second experiment, a set of 79,132 single nucleotide polymorphisms (SNPs) markers were used in an association study to identify genomic regions underlying stalk rot resistance using a multi-locus mixed model association mapping approach. We identified 14 loci associated with stalk rot and a set of candidate genes that appear to be involved in connected functions controlling plant defense response to stalk rot resistance. The associated SNPs accounted for 19-30% of phenotypic variation observed within and across environments. An analysis of associated allele frequencies within the major sorghum subpopulations revealed enrichment for resistant alleles in the durra and caudatum subpopulations compared with other subpopulations. The findings suggest a complicated molecular mechanism of resistance to stalk rots. The objective of the third experiment was to determine the functional relationship between stay-green trait, leaf dhurrin and soluble sugar levels and resistance to stalk rot diseases. Fourteen genotypic groups derived from a Tx642 × Tx7000 RIL population carrying combinations of stay-green quantitative trait loci were evaluated under three environments in four replications. The stg QTL had variable effects on stalk rot disease. Genotypes carrying stg1, stg3, stg1,3 and stg1,2,3,4 expressed good levels of resistance to M. phaseolina but the combination of stg1 and stg3 was required to express the same level of resistance to F. thapsinum. Other stg QTL blocks such as stg2 and stg4 did not have any impact on stalk rot resistance caused by both pathogens. There were no significant correlations between leaf dhurrin, soluble sugar concentration, and resistance to any of the pathogens.
Keywords: Sorghum; Fusarium thapsinum; Macrophomina phaseolina; Stalk rot; Stay-green; Association mapping; Agronomy (0285); Bioinformatics (0715); Pathology (0571)